Perlindungan Hukum bagi Pekerja Penyandang Disabilitas pada PT. Sumber Alfaria Trijaya - I Wayan Tika Tambunan; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Jurnal Interpretasi Hukum, 2020)
At present, there are cases of persons with disabilities being employed in a retail company in the Bali area. The Manpower Act provides provisions for companies to employ people with disabilities. Therefore, companies are required to provide accessibility. This research was conducted with the aim of describing the implementation of legal protection for workers with disabilities at PT. Sumber Alfaria Trijaya based on Law Number 13 2003 and the factors that become obstacles in the application of legal protection for workers with disabilities at PT. Source Alfaria Trijaya. The research method used is an empirical legal research method with a factual approach and a statutory approach. Based on the results of data analysis, the implementation of legal protection provided by PT. Sumber Alfaria Trijaya towards workers with disabilities has not been fulfilled, namely in terms of providing qualified accessibility. Several factors inhibiting the implementation of legal protection efforts for workers with disabilities, namely the law enforcement factor itself and the community factor. So the government is expected to further optimize the supervision of companies that have not implemented the mandate of the law and provide socialization and guidance to companies and workers on the importance of rights and obligations.